Analisis Pengaruh Biaya Operasional Pendapatan Operasional Dan Net Profit Margin Terhadap Pertumbuhan Laba Pada Bank Mandiri - Marangga Mantika; Alwi Alwi; Nafisah Nurulrahmatia (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of operating costs, operating income, and Net Profit Margin (NPM) on profit growth at PT Bank Mandiri (Persero) Tbk. The study uses secondary data in the form of annual financial statements, which are analyzed using a quantitative approach. The analytical methods employed include multiple linear regression, partial testing (t-test), simultaneous testing (F-test), and the coefficient of determination to measure the contribution of each variable to profit growth. The results indicate that operating costs have a negative and significant effect on profit growth, suggesting that an increase in operating costs can reduce the bank’s profitability performance. In contrast, operating income and Net Profit Margin (NPM) have a positive and significant impact on profit growth, indicating that higher operating income and efficient profit management play an important role in improving the company’s financial performance. Simultaneously, operating costs, operating income, and NPM have a significant effect with a substantial contribution to profit growth, while the remaining variation is explained by other factors outside the research model. These findings emphasize the importance of cost efficiency, increasing operating income, and strengthening profit margins to ensure Bank Mandiri remains competitive in the increasingly intense national banking industry.